Naval Autonomous Systems: Strategic Technology or Costly Showpieces? - Balakrishnan, Ramesh (2017)
In recent years many demonstrations of prototypes have been held to showcase futuristic autonomous technologies such as unmanned naval systems/drones. Both the US and UK, on the one hand, as well as Russia and China, on the other, have tested their autonomous naval systems. What does this autonomous technology revolution at sea mean for strategic stability in the maritime commons?